Assessment of a novel patient reported outcome measure for visual snow syndrome: the Colorado visual snow survey 2.0 - Maione, Samuel M.; Pelak, Victoria S.; Gerhardstein, Peter (Frontiers in Neurology, 2025)
IntroductionVisual snow syndrome (VSS) is a condition in which people experience a continuous overlay of small dots atop their entire visual field. As a newly recognized condition, there is a gap in patient reported outcome measures (PROMs) that target VSS symptom impact.MethodsWe sought to assess the Colorado Visual Snow Survey 2.0 (CVSS) as a possible PROM for VSS using a convenience sample of undergraduate students and people with VSS recruited through the Visual Snow Initiative (N = 144).ResultsWe found the CVSS (1) strongly differentiated people with VSS from healthy controls, (2) demonstrated high internal consistency, and (3) aside from visual static, the degree of night vision impairment, blue field entoptic phenomenon, and afterimages, and tinnitus (in that order) best predicted group membership. We also find evidence to suggest people with VSS may be more sensitive to entoptic phenomenon and depersonalization/derealization than control participants.ConclusionOverall, CVSS is a promising PROM that warrants further validation.